TRANSFORMATIONAL LEADERSHIP IN IMPROVING PUBLIC ORGANISATION PERFORMANCE - Erwin Erwin; Melyana R Pugu; Amândio de Araújo Sarmento; Al-Amin; Mohd Syahrin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Transformational leadership is a leadership style in which the leader inspires and motivates employees to exceed their expectations by creating a compelling long-term vision, promoting innovation, and embedding ethical values and integrity in the organisation's culture. In this leadership, leaders focus on the personal development of employees, empowering them to take initiative and think creatively, with the ultimate goal of improving organisational performance and adaptability in the face of challenges and change. The research method used is literature research method. The results of the literature analysis show that transformational leadership has various positive impacts on the performance of public organisations. First, transformational leaders are able to increase employee motivation and commitment through inspiring communication and providing positive feedback, which has an impact on increasing productivity and job satisfaction. Second, transformational leadership contributes to the development of a strong organisational culture, prioritising ethical values and integrity, which is important in improving accountability and transparency in the public sector. Third, transformational leaders make organisations more adaptive and responsive to change by empowering employees to think creatively and proactively.